Dyspareunia in Postmenopausal Women: A Critical Review - Alina Kao; Yitzchak M Binik; Anita Kapuscinski; Samir Khalifé (Pain Research and Management)
BACKGROUND: Dyspareunia, or pain during sexual intercourse, is among the problems most frequently reported by postmenopausal women. Past literature has almost unanimously attributed dyspareunic pain occurring during or after the menopausal transition to declining estrogen levels and vaginal atrophy.